Investigation of aluminum heat sink design with thermoelectric generator - Mohiuddin, A. K. M.; Amer, Muhammad Yazid; Rahman, Mohammed Ataur; Khan, Ahsan Ali (IOP Publishing Ltd., 2017)
This paper presents an investigation of aluminium heat sink designs with thermoelectric generator. Basically, for thermoelectric generator (Peltier module), the thermal conversion uses Peltier effect. Two heat sinks with different design, with thermoelectric module of Bismuth Telluride, Bi 2 Te 3 were used in this investigation. The simulation and experimental studies were conducted with two different heat sinks attached with thermoelectric generator (TEG). System modelling was used to collect data and to predict the behaviour and performance of thermoelectric modules. Experiment was conducted in exhaust system at muffler section since the temperature at muffler section meets the requirement of thermoelectric generator.The result of the experiments shows that rectangular fin heat sink is more efficient in heat transfer compared to circular tube fin heat sink due to its geometry and properties.